Encuentros sexuales, espacios escolares y heteronorma (2018)
This work seeks to reflect how school spaces in certain contexts and moments can become sexualized spaces. Through the narratives of three young college students, it will be discussed as educational spaces can be sites that are used to perform erotic pleasure. They will address some of the codes that are generated around these practices and forms of appropriation of space. It will also reflect as despite the existence of heteronormative sexual encounters in schools are a phenomenon that persists and that transcends gender and sexual orientation.